MENINGKATKAN PRESTASI BELAJAR IPS TENTANG JENIS-JENIS PEKERJAAN MELALUI PEMBUATAN KLIPING - subiah subiah (Program Pascasarjana Universitas Islam Darul `Ulum Lamongan, 2020)
This study was aimed to investigate the implementation of learning by making clipping in enhancing the learning and achievement of Social about the types of job through the creation of clipping. The study used classroom action research method which consisted of several cycles with each cycle there are planning, action, observation, and reflexion. The subjects were all of the third graders of The Second State Elementary School of Katemas, Kembangbahu District, Lamongan in the academic year of 2015/2016 in second semester in sum of 10 people. The result showed that learning by making clipping can improve the learning achievement of Social. It is characterized by an increase in students' mastery of classical study in the first cycle (60%) and the second cycle (100%) and the increase in the average value of students is 5.85 at 81.00 on the first cycle to the second cycle.